Implementasi Kebijakan Kesehatan Publik pada Pelayanan Kesehatan Primer dan Tantangannya dalam Mewujudkan Sistem Kesehatan Nasional yang Berkelanjutan - Abim Sastrawan; Fadila Amalia Rahmah (Jurnal Intelek Insan Cendikia, 2026)
This study aims to analyze the implementation of public health policies in primary health care services and the challenges in achieving a sustainable national health system. A qualitative descriptive approach was employed, utilizing secondary data and policy documentation from 2020–2025. Data were analyzed using the interactive model of Miles and Huberman, including data reduction, data display, and conclusion drawing. The findings reveal three main themes: limited operational clarity of policy goals and standards, constraints in capacity and resources of implementers, and variations in the disposition and understanding of policy actors at the primary care level. These findings contribute to a deeper understanding of health policy implementation as a contextual and socially embedded process. The study highlights the need for strengthening institutional capacity, improving policy coherence, and adopting context-sensitive approaches to enhance the sustainability of the national health system